Bio Analytical Method Development for Analysis of Apremilast in Rat Plasma Using Reverse Phase HPLC-UV for Bioequivalence and Pharmacokinetic Application. Issue 6 (1st November 2020) - Tamilselvi, N.; Nishanth, R.; Gopalasatheeskumar, K.
Abstract: Apremilast (APR) is one of the drugs used for the treatment of patients with several immune- inflammatory conditions. Currently, the APR is available for the treatment of psoriasis and psoriatic arthritis. This research was aimed to develop the bio-analytical method for estimation of APR and its bioequivalence and pharmacokinetics using the RP-HPLC-UV method. The method was as per USFDA guidelines and analyzing APR in rat plasma by oral administration in rats. Aplex 30 mg tablet was taken as a reference product to evaluate the pharmacokinetic profile of the Alizap 30 mg tablet which was taken as a test product. The Cmax for the test product and reference product was found to be 154.85±1.34 and 168.54±1.78 ng/ml respectively. The tmax for test and reference product was found to be 15±0.17 min respectively. AUC0-t for test and reference product was found to be 32248.52±8.10 and 33746.83±17.64 ng/ml. AUC0-∞  for test and reference product was found to be 32248.52±10.52 and 42210.61±14.32 ng/ml respectively. The T1/2 for test product and reference product was found to be 134.45±1.30 and 175.87±1.47 respectively. The pharmacokinetic study shows no significant (p > 0.05) difference by statistical analysis between two products and hence Aplex 30 mg (Reference product) was found to be bioequivalent to Alizap 30 mg (Test product).